(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In this article, the main emphasis in the formation of the export product strategy of the enterprise is placed on the effective formation and management of the product range, the timely provision of a set of products that most fully meets the needs of consumers.